2002
DOI: 10.2307/3079081
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Simple Rule for Dominance in Resource Competition

Abstract: Competition for limiting resources long has been considered an important factor generating community structure. A minimal model of resource competition predicts that the species that reduces the limiting resource R to the lowest level ([Formula: see text]) will exclude its competitors. Whether this "[Formula: see text] rule" is robust to violations of model assumptions remains largely unknown. I conducted a competition experiment with four species of bacterivorous protists in laboratory microcosms and predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 0 publications
4
61
2
Order By: Relevance
“…Theory concurs, indicating that the paradox of enrichment may disappear with the inclusion of heterogeneity in edibility or vulnerability to predators, competitive interactions among consumer species, or spatial refuges (Abrams 1993, Grover 1995, Scheffer and de Boer 1995, Leibold 1996, McCann et al 1998, Murdoch et al 1998, Morin 1999). While we can only speculate as to which explanation might be most relevant to the pitcher plant fauna of this study, the microfaunal consumer level is clearly heterogeneous (different growth rates and food preferences), as is the basal level (various bacterial types: Cochran‐Stafira and von Ende 1998, Fox 2002), and the activity of midges may further alter the composition of the bacterial guild. In addition, there is likely competition among some microfauna (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Theory concurs, indicating that the paradox of enrichment may disappear with the inclusion of heterogeneity in edibility or vulnerability to predators, competitive interactions among consumer species, or spatial refuges (Abrams 1993, Grover 1995, Scheffer and de Boer 1995, Leibold 1996, McCann et al 1998, Murdoch et al 1998, Morin 1999). While we can only speculate as to which explanation might be most relevant to the pitcher plant fauna of this study, the microfaunal consumer level is clearly heterogeneous (different growth rates and food preferences), as is the basal level (various bacterial types: Cochran‐Stafira and von Ende 1998, Fox 2002), and the activity of midges may further alter the composition of the bacterial guild. In addition, there is likely competition among some microfauna (e.g.…”
Section: Discussionmentioning
confidence: 90%
“…Many studies have found support for the R* principle, including microcosm studies that investigated competitive outcomes with heterotrophic protists (Fox 2002). Given that resource consumption is the basis for metabolic power, the R* principle and the MPP may be invoking essentially the same processes.…”
Section: Discussionmentioning
confidence: 99%
“…The four productivity levels respectively comprised 0.01, 0.1, 0.55 or 1 g PP l −1 . These productivity levels span a range known to strongly affect protist densities (Kaunzinger and Morin 1998, Fox 2002, Fukami and Morin 2003). The two lowest productivity levels had 1/4 wheat seed dish −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Further, in many systems the predictability of secondary succession and the consistency with which certain species dominate in certain environments indicates that initial conditions are of little importance (Tuomisto et al 2003). Instead, final community composition in these systems is a predictable reflection of species’ traits, such as competitive ability for different limiting resources (Tilman 1982, Fox 2002, Adams et al 2007).…”
mentioning
confidence: 99%